Effects and functional mechanisms of digital fitness platforms on online fitness payment behavior under the perspective of "She-economy". - Kaidi Zhang; Tao Yang; Zhipeng Liu; Cuixia Yi; Yueyun Hou; Tianyi Wu (PLoS ONE)
Women have become an important force for economic development. Online fitness payment behavior is an important part of women's pursuit of "beautiful skin and healthy body", and is also an important embodiment of the integration of the digital industry and the fitness industry. Based on Stimuli-Organism-Response and Technology Acceptance Model theories, this study systematically explored the relationship and mechanism of action between digital fitness platforms and online fitness payment behavior through a survey of 259 women using Structural Equation Modeling and Fuzzy Set Qualitative Comparative Analysis. It was found that women's perceived use of digital fitness platforms was positively related to satisfaction, continued use intention, and online fitness payment behavior, except for the relationship between perceived usefulness and satisfaction, which was not significant. With the exception of satisfaction, which did not mediate between perceived enjoyment and online fitness payment behavior, satisfaction, and continued using intention mediated and chained mediation between the other independent variables and the dependent variable. The "comprehensive" digital fitness platforms were the most popular and favorite among women, followed by the "hedonic" and "pragmatic" platforms. On this basis, corresponding countermeasures and recommendations are proposed to promote the healthy, sustainable, and stable development of the digital fitness industry.